Optimalisasi Gerakan Masyarakat Dalam Proses Analisa Faktor Penyebab Stunting (0-24 Bulan) di Desa Jarit Kecamatan Candipuro - Novianti, Azizah; Nurmanda, Pravita Salbia; Ummam, Naufa Izzul; Fernandes, Jose Frangelino Borges; Muflihah (Community: Jurnal Pengabdian Kepada Masyarakat, 2024)
Reducing the stunting rate is one of the programs being carried out by the government of the Republic of Indonesia. By mobilizing all existing components of society, the prevalence of stunting in Indonesia in 2024 is expected to decrease to 14%. Based on these reasons, the public as the main object in the presidential order is expected to intervene by knowing what causes stunting and how to overcome and cure it. This research was conducted in Jarit Village, Candipuro sub-district, Lumajang district, East Java using the CBR (Community Based Research) method. The method of presenting the data is descriptive-qualitative and analyzed by comparing the data obtained from the literature review process. The conclusion obtained in this study is that mothers of toddlers who are infected with stunting in Jarit village do not apply the parenting pattern that should be applied to their children. The innovation that is applied related to handling these problems is to apply GEMAS as an application from a community-based movement that focuses on handling stunting.